Synonymization of the genus nomen Dendroplex Swainson, 1827 and description of a new genus of woodcreeper (Aves: Passeriformes: Dendrocolaptidae) with remarks on Articles 67.5 and 70.3 of the Code - Raposo, Marcos A.; Dubois, Alain; Kirwan, Guy M.; de Assis, Claydson Pinto; Höfling, Elizabeth; Stopiglia, Renata (Zootaxa, 2018)
The polytypic Straight-billed Woodcreeper Dendroplex picus (J. F. Gmelin, 1788) is one of the most complex species-groups of Dendrocolaptidae (Aves: Passeriformes), from both the nomenclatural and morphological standpoints. Firstly, its alpha taxonomy is debatable. Virtually all recent works (e.g. Aleixo 2002; Marantz et al. 2003; del Hoyo & Collar 2016) have recognized just two species in the group—Dendroplex picus and Zimmer’s Woodcreeper Dendroplex kienerii (Des Murs, 1856)—although some of the other described taxa possess singular morphological characters and well-defined ranges somewhat isolated from their geographically closest relatives (e.g. Plain-throated Woodcreeper Dendroplex picirostris Lafresnaye, 1847). Secondly, the correct genus to which to allocate taxa presently included in this group (vide Aleixo 2002) has been controversial. There is a considerable confusion as to which nominal species should be regarded as the type of Dendroplex Swainson, 1827b. Three species are involved in the dispute (Cory & Hellmayr 1925; Peters 1951; Aleixo et al. 2002; Marantz et al. 2003; Aleixo et al. 2007): Oriolus picus J. F. Gmelin, 1788; Dendrocolaptes guttatus M. H. C. Lichtenstein, 1818; and Dendrocolaptes ocellatus Spix, 1824. Here, we re-examine the nomenclatural issue and show that application of the nomen Dendroplex to the clade comprising the species-group D. picus (Aleixo et al. 2007) is based on a misunderstanding of the application of Article 70.3 of the Code (Anon. 1999) and that Dendrocolaptes ocellatus Spix, 1824, is its real type species. Consequently, the genus Dendroplex Swainson, 1827b, must be considered a junior synonym of Xiphorhynchus Swainson, 1827a. Because no generic nomen is currently available for them, we propose a new genus nomen to encompass the species originally described as Oriolus picus J. F. Gmelin, 1788, Dendroplex picirostris Lafresnaye, 1847, and Dendrornis kienerii Des Murs, 1856.